Semantic Analysis Of Poetry “Fear No More The Heat O’ The Sun” By William Shakespeare - Said, Ratna; Oktariyani, Oktariyani; Usman, Rahmi; Djafar, Rahmi (JUPE : Jurnal Pendidikan Mandala, 2023)
Classical poetry is still very popular today. But in this classic piece of literature, especially in William Shakespeare's poem "Fear No More the Heat of the Sun," it can be difficult to understand what the words mean. Therefore, this study aims to help poetry lovers understand the meaning of poetry using semantic analysis that focuses on the lexical meaning and denotation meaning. The dates in this sentence are the words of his four stanza verses of the poem which is the basic level of attention. The data acquisition technique is to reread each word many times. The data obtained were analyzed using dictionaries and encyclopedias. The results of this study were Poetry Fear No More The Heat O' The Sun By William Shakespeare Tells The Story Of Chimney Sweepers in this study was dominated by lexical meaning.